Study of b⟶c Induced B¯∗⟶Vℓν¯ℓ Decays - Qin Chang; Xiao-Lin Wang; Jie Zhu; Xiao-Nan Li (Advances in High Energy Physics)
In this paper, we investigate the tree-dominated B¯u,d,s,c∗⟶Vℓ−ν¯ℓ (V=Du,d∗,Ds∗,J/ψ and ℓ=e,μ,τ) decays in the Standard Model with the relevant form factors obtained in the light-front quark model. These decays involve much more helicity states relative to the corresponding B¯∗⟶Pℓ−ν¯ℓ and B¯⟶Vℓ−ν¯ℓ decays, and moreover, the contribution of longitudinal polarization mode (V meson) is relatively small, ~30%, compared with the corresponding B meson decays. We have also computed the branching fraction, lepton spin asymmetry, forward-backward asymmetry, and ratio RV∗L≡BB¯∗⟶Vτ−ν¯τ/BB¯∗⟶Vℓ′−ν¯ℓ′ℓ′=e,μ. Numerically, the branching fractions of B¯∗⟶Vℓ′−ν¯ℓ′ decays are at the level of O10−7 and are hopeful to be observed by LHC and Belle-II experiments. The ratios RD∗,Ds∗,J/ψ∗L have relatively small theoretical uncertainties and are close to each other, RD∗∗L≃RDs∗∗L≃RJ/ψ∗L≃0.26,0.270.27,0.29, which are a bit different from the predictions in some previous works. The future measurements are expected to make tests on these predictions.